2003
DOI: 10.1099/jmm.0.05056-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of 11 pathogenic genes of Campylobacter jejuni by PCR in strains isolated from humans, poultry meat and broiler and bovine faeces

Abstract: Although many genes related to the pathogenicity of Campylobacter jejuni have been reported, the relationships between these genes and the sources of strains are not clear. In this study, the presence of 11 pathogenic genes responsible for the expression of adherence, invasion, colonization and cytotoxin production was examined in 111 C. jejuni isolated from human clinical samples, poultry meat, broiler faeces and bovine faeces. For most of the pathogenic genes, no difference in their presence in C. jejuni was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

34
120
6
14

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 173 publications
(174 citation statements)
references
References 16 publications
34
120
6
14
Order By: Relevance
“…In contrast, several studies have shown wide variations for the presence of virB11, which was not found in C. jejuni and C. coli isolates from poultry faeces, 18 although it was identified in 4% to 15% of isolates tested from poultry meat, pig and cattle, 31,32,36 and in 10% to 17% of human clinical samples. 31,38 However, the prevalence of the plasmid pVir appears to be similar among poultry and human isolates. 17,31,38 The production of the pVir plasmid genes in the C. coli 26536 clinical isolate used in the present study thus indicates the possibility of severe invasive infection.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…In contrast, several studies have shown wide variations for the presence of virB11, which was not found in C. jejuni and C. coli isolates from poultry faeces, 18 although it was identified in 4% to 15% of isolates tested from poultry meat, pig and cattle, 31,32,36 and in 10% to 17% of human clinical samples. 31,38 However, the prevalence of the plasmid pVir appears to be similar among poultry and human isolates. 17,31,38 The production of the pVir plasmid genes in the C. coli 26536 clinical isolate used in the present study thus indicates the possibility of severe invasive infection.…”
Section: Discussionmentioning
confidence: 79%
“…30,31,37 The cadF gene is probably conserved among Campylobacter spp isolates, 18 regardless of their origin or species, as is the case also in the C. coli 26536 isolate used here. In contrast, several studies have shown wide variations for the presence of virB11, which was not found in C. jejuni and C. coli isolates from poultry faeces, 18 although it was identified in 4% to 15% of isolates tested from poultry meat, pig and cattle, 31,32,36 and in 10% to 17% of human clinical samples. 31,38 However, the prevalence of the plasmid pVir appears to be similar among poultry and human isolates.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations